Характеристика розвитку промислового підприємства - Білопольський, М.Г.; Харченко, В.А. (Економічний вісник Донбасу, 2014)
У статті виокремлено цілі розвитку промислового підприємства залежно від рівнів управління, стратегій управління, видів розвитку та підсистем управління, узгоджено цілі розвитку за різними об’єктами класифікаційних ознак, що дозволяє забезпечити максимальний ефект від процесу розвитку і управління діяльністю у діючих умовах господарювання. В статье выделены цели развития промышленного предприятия в зависимости от уровней управления, стратегий управления, видов развития и подсистем управления, согласованы цели развития по разным объектам классификационных признаков, что позволяет обеспечить максимальный эффект от процесса развития и управления деятельностью в действующих условиях хозяйствования. The article aims at determining the main purposes of the industrial enterprise development (on the basis of theoretic generalization of scientists’ views on the notion ‘development’), which are realized in the management system of its development. There has been studied the evolution of scientific opinions concerning the definition of the notion ‘development’ from classicism to institutionalism, including neo-Keynesian and neo-classicism. There have been generalized the existing models and theories of development at macro- and microlevels, in which development is interconnected with the notions ‘growth’ and ‘functioning’.
There have been determined the connections between equal categories: development, growth, functioning, change, evolution and progress. On the basis of classification features there have been suggested the main notional differences between these equal categories. There has been agreed the use of notions development, growth, functioning, change, evolution and progress with basic notions characterizing an industrial enterprise: activity, markets, price, profit.
There has been defined that the term ‘development’ in a generalized form is studied as a process (of adaptation, transition, movement, improvement), as changes (in time, of state, global aims of an enterprise) and as a set of changes. There have been discussed the questions of development boundaries: its beginning and end. It has been grounded that the end of development starts when the aims of development are achieved during the realization of managerial decisions in the control system of industrial enterprises’ development.
There has been suggested the aggregate of aims of enterprise development that are classified according to four characteristics: 1) depending on the subsystem of inner state of an enterprise (production subsystems and production realization, subsystems of financial state and subsystems of resource state); 2) depending on the management levels (strategic, innovative and operating); 3) depending on the management strategy (aggressive, moderate and conservative); 4) depending on the types of development (technological, economic, financial, information, ecological and social).